1994
DOI: 10.1042/bj3020527
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the small interstitial proteoglycans biglycan, decorin and fibromodulin with transforming growth factor β

Abstract: We have analysed the interactions of three proteoglycans of the decorin family, decorin, biglycan and fibromodulin, with transforming growth factor beta (TGF-beta). The proteoglycan core proteins, expressed from human cDNAs as fusion proteins with Escherichia coli maltose-binding protein, each bound TGF-beta 1. They showed only negligible binding to several other growth factors. Intact decorin, biglycan and fibromodulin isolated from bovine tissues competed with the fusion proteins for the TGF-beta binding. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
704
5
22

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 938 publications
(751 citation statements)
references
References 52 publications
20
704
5
22
Order By: Relevance
“…Taken together, these results indicate that biglycan acts as a co‐receptor in the TGF‐β 1 –ALK5–Smad2/3 system and is involved in the downregulation of syndecan‐4 expression in vascular endothelial cells. Biglycan has been reported to bind not only TGF‐β 1 [Hildebrand et al, 1994] but also other cytokines such as tumor necrosis factor‐α [Tufvesson and Westergren‐Thorsson, 2002] and receptors [Schaefer et al, 2005]. The present study, for the first time, revealed that biglycan serves as a co‐receptor in TGF‐β signaling and this signaling downregulates the expression of syndecan‐4 in vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Taken together, these results indicate that biglycan acts as a co‐receptor in the TGF‐β 1 –ALK5–Smad2/3 system and is involved in the downregulation of syndecan‐4 expression in vascular endothelial cells. Biglycan has been reported to bind not only TGF‐β 1 [Hildebrand et al, 1994] but also other cytokines such as tumor necrosis factor‐α [Tufvesson and Westergren‐Thorsson, 2002] and receptors [Schaefer et al, 2005]. The present study, for the first time, revealed that biglycan serves as a co‐receptor in TGF‐β signaling and this signaling downregulates the expression of syndecan‐4 in vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 56%
“…3), because an interaction between biglycan and TGF‐β 1 has been reported [Hildebrand et al, 1994]. TGF‐β 1 elevated the expression levels of syndecan‐4 mRNA after a 3‐h treatment at 1 and 5 ng/mL or after a 6‐h treatment at 5 ng/mL (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Indeed, by expressing collagens and fibronectin essential for assembling conduits, FDC may help to regulate the transport of low-molecular-weight proteins [32]. The pericellular localization of biglycan (Fig 4A) is in line with the notion that biglycan functions as an extracellular regulator of cytokines and growth factors [29][30].Beyond this, FDC may contribute to the mobility of B cells in the GC. Thus, two-photon microscopy has shown that fibroblastic reticular cells guide the migration of T cell through the T-cell zone [33] and FDC may regulate B-cell motility in a similar way [34,35].…”
supporting
confidence: 59%
“…3), known to control the availability of cytokines, chemokines and growth factors [29][30][31]. Indeed, by expressing collagens and fibronectin essential for assembling conduits, FDC may help to regulate the transport of low-molecular-weight proteins [32].…”
Section: Discussionmentioning
confidence: 99%
“…Bgn and Dcn belong to the class I type SLRP and are highly expressed in skeletal and connective tissues (1,12,14,15,31). The exact function of both Bgn and Dcn are unknown, however both can bind and modulate members of the TGF-beta superfamily (11).…”
Section: Introductionmentioning
confidence: 99%